Matching supplementary motor area-primary motor cortex paired transcranial magnetic stimulation improves motor dysfunction in Parkinson’s disease: a single-center, double-blind randomized controlled clinical trial protocol - Tang, Xiaoshun; Huang, Zhexue; Zhu, Guangyue; Liang, Haoyuan; Sun, Hui; Zhang, Yu; Tan, Yalin; Cui, Minglong; Gong, Haiyan; Wang, Xijin; Chen, Yu-Hui (Frontiers in Aging Neuroscience, 2024)
Background Non-invasive neuroregulation techniques have been demonstrated to improve certain motor symptoms in Parkinson’s disease (PD). However, the currently employed regulatory techniques primarily concentrate on stimulating single target points, neglecting the functional regulation of networks and circuits. The supplementary motor area (SMA) has a significant value in motor control, and its functionality is often impaired in patients with PD. The matching SMA-primary motor cortex (M1) paired transcranial magnetic stimulation (TMS) treatment protocol, which benefits patients by modulating the sequential and functional connections between the SMA and M1, was elucidated in this study. Methods This was a single-center, double-blind, randomized controlled clinical trial. We recruited 78 subjects and allocated them in a 1:1 ratio by stratified randomization into the paired stimulation (n = 39) and conventional stimulation groups (n = 39). Each patient underwent 3 weeks of matching SMA-M1 paired TMS or sham-paired stimulation. The subjects were evaluated before treatment initiation, 3 weeks into the intervention, and 3 months after the cessation of therapy. The primary outcome measure in this study was the Unified Parkinson’s Disease Rating Scale III, and the secondary outcome measures included non-motor functional assessment, quality of life (Parkinson’s Disease Questionnaire-39), and objective assessments (electromyography and functional near-infrared spectroscopy). Discussion Clinical protocols aimed at single targets using non-invasive neuroregulation techniques often improve only one function. Emphasizing the circuit and network regulation in PD is important for enhancing the effectiveness of TMS rehabilitation. Pairing the regulation of cortical circuits may be a potential treatment method for PD. As a crucial node in motor control, the SMA has direct fiber connections with basal ganglia circuits and complex fiber connections with M1, which are responsible for motor execution. SMA regulation may indirectly regulate the function of basal ganglia circuits. Therefore, the developed cortical pairing stimulation pattern can reshape the control of information flow from the SMA to M1. The novel neuroregulation model designed for this study is based on the circuit mechanisms of PD and previous research results, with a scientific foundation and the potential to be a means of neuroregulation for PD. Clinical trial registration: ClinicalTrials.gov, identifier [ChiCTR2400083325].